Hubungan body image dengan kualitas hidup pada pasien kanker payudara yang menjalankan kemoterapi - Fitri Haryati; Dian Nur Adkhana Sari (Health Sciences and Pharmacy Journal, 2019)
Breast cancer ranks first in the number of cases of cancer as well as the biggest cause of death due to cancer in the world each year. Breast cancer is a malignant tumor that is at risk of affecting body image. Quality of life is the concept of analyzing the ability of individuals to get a normal life. This study is to know there is a relationship between body image with quality of life in breast cancer patients (ca mammae) who run chemotherapy in RSUD Panembahan Senopati Bantul Yogyakarta. This research used correlation design with cross sectional approach. The population in this research was breast cancer patient (camammae) who run chemotherapy. The samples were 30 breast cancer patients (camammae) with accidental sampling techniques, instruments used Body Image Satisfaction (BIS) and The World Health Organization Quality of Life (WHOQOL)-BREF. The results were analyzed by Kendall's Tau test. The results of this study showed that the body image in the category was mostly 22 people (73.3%), while the quality of life in breast cancer patients (camammae) who run chemotherapy mostly included in the category both with percentage (70.0%) of 21 people. Kendall's Tau test results obtained correlation coefficient = 0.966 and with significance p = 0.000 0.01 (significance level). There was a relationship between body image with quality of life in breast cancer patients (camammae) who run chemotherapy.